The use of social networking website containing visual materials in education = Wykorzystanie społecznościowego serwisu materiałów wizualnych w edukacji - Šimik, Ondřej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article describes possibilities of using the networking website Pinterest (designed for collecting visual content) in education. Pinterest is a collection of virtual boards with photos shared by its users. The shared pictures ("pins") can be grouped and categorized along different criteria. The collected resources can be catalogues of inspiration and ideas also in education. The article presents the possible ways of using the website in teaching integrated subjects in primary schools. It also shows pupils? competences which can be developed with the use of the website and the educational aims which are realised in this process.
Keywords: Pinterest; edukacja; technologie informacyjne; technologie komunikacyjne; kształcenie zintegrowane; szkolnictwo podstawowe; education; communication technologies; information technologies; integrated education; primary school